The Structure-Conduct-Performance Paradigm in the Indonesian Manufacturing Industry - Yuliati, Lilis; Adenan, Moh.; Prianto, Fajar Wahyu; Wibisono, Sunlip; Komariyah, Siti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
This study examines the structure, conduct, and performance (SCP) of the Indonesian manufacturing industry, contributing the most to the national economy from 2017 to 2021. The research employed SCP analysis, which entails evaluating market concentration using the Herfindahl Hirschman Index (HHI) and analyzing market performance and industry behavior utilizing literature reviews. Based on Indonesian Central Statistics Agency groupings, the sample data covers 23 sub-sectors of the manufacturing industry. The results of the HHI calculations also show that the concentration of the manufacturing industry market is at a moderate level, mergers and acquisitions that result in moderate market concentration of HHI enhancements will raise anti-competitive concerns and will require further analysis and often require scrutiny. Hence, requiring proper supervision and strategy in developing competitiveness amidst global uncertainty. The conduct and performance of the manufacturing industry show an effort to grow better amid fairly tight global competition. Therefore, it is necessary for a number of parties to play a part in boosting productivity and the competitiveness of goods produced by the manufacturing sector. Governments should reduce their direct intervention in the market by implementing industrial policies and seeking market-oriented policy means to influence the economy.